Meta-Analysis: Association between Empowerment of Home-Based Rehabilitation Intervention on the Escalation of Functional Ability in Post Stroke Patients - Syawaludin, Muhammad Husein; Sumardiyono, Sumardiyono; Murti, Bhisma (Journal of Health Policy and Management, 2022)
Background: Stroke is a disease that is the third leading cause of death in the world after heart and cancer. Stroke is also a disease that causes serious and permanent disability in the first order in the world. The rehabilitation program or recovery of stroke patients will greatly affect the improvement of functional abilities and independence of post-stroke patients, one of the keys to functional improvement is the intensity of therapy and family involvement in supporting the rehabilitation process. This study aims to analyze the relationship between empowering home-based recovery interventions to improve the functional ability of post-stroke patients, with a meta-analysis of primary studies conducted by previous authors.Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, Population: stroke patients. Intervention: home-based recovery. Comparison: not home based recovery. Outcomes: functional ability. The articles used in this study were obtained from several databases, namely PubMed, Springer Link, Cochrane Database, Hindawi, Elsevier, JBBA, LWW, Google Scholar. Search keywords “home-based” AND “intervention” OR “rehabilitation” OR “exercise” OR “therapy” OR “care” AND “stroke” AND “functional ability” OR “functional capacity” AND “Randomized Controlled Trial “ OR “ RCT". The articles included are full-text English and Indonesian languages with a study design of a Randomized Controlled Trial from 2000 to 2021 and reporting on the Mean and SD in multivariate analysis. The selection of articles is done by using PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 9 randomized controlled trials from Iran, Turkey, Australia, Taiwan, China, Thailand and the Netherlands were selected for a systematic review and meta-analysis. The data collected showed that the home-based recovery intervention improved functional ability in post-stroke patients compared to usual care (SMD = 2.70; 95% CI = 1.53 to 3.87; p<0.001). There is a publication bias that indicates an overestimation). Conclusion: Home-based recovery interventions improve functional ability in post-stroke patients.Keywords: Home-based recovery, functional ability, stroke patients, meta-analysisCorrespondence: Muhammad Husein Syawaludin. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: fahusein26@gmail.com. Mobile: +6285728989309.Journal of Health Policy and Management (2022), 07(01): 46-57https://doi.org/10.26911/thejhpm.2022.07.01.05